1999
DOI: 10.1103/physrevb.59.r10425
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the negatively and positively charged excitons in GaAs quantum wells

Abstract: We compare the photoluminescence spectra of the negatively and positively charged excitons in GaAs quantum wells. We use a structure which enables us to observe both complexes within the same sample. We find that their binding energy and Zeeman splitting are very similar at zero magnetic field, but evolve very differently at high fields. We discuss the implications of these observations on our understanding of the charge excitons structure in high magnetic fields. ͓S0163-1829͑99͒51516-6͔

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
112
2

Year Published

2001
2001
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 16 publications
19
112
2
Order By: Relevance
“…4. Moreover this result is also in agreement with the experimental results which showed that the energy of the X + is larger 13,14 or equal 19 to the one of X − . Stébé and Moradi 6 found, on the other hand, that for a 300Å wide quantum well the binding energy of X + is lower than the one of X − which is opposite to our conclusion and to those of Ref.…”
Section: Zero Magnetic Field Trion Energysupporting
confidence: 82%
See 2 more Smart Citations
“…4. Moreover this result is also in agreement with the experimental results which showed that the energy of the X + is larger 13,14 or equal 19 to the one of X − . Stébé and Moradi 6 found, on the other hand, that for a 300Å wide quantum well the binding energy of X + is lower than the one of X − which is opposite to our conclusion and to those of Ref.…”
Section: Zero Magnetic Field Trion Energysupporting
confidence: 82%
“…3, we compare the binding energy of the X + and of the X − singlet state for a 200Å wide quantum well with the experimental results obtained by Glasberg et al 19 and the very recent results Yusa et al 24 (open triangles). When comparing the experimental results with our theoretical results we notice that for B = 0 the experimental and theoretical result for the negatively charged exciton binding energy differ by about 0.3 meV, which may be due to a non-zero density effect and/or to localization induced by quantum well width fluctuation.…”
Section: Comparison With Experimentsmentioning
confidence: 95%
See 1 more Smart Citation
“…This makes the observation of the X − a difficult task only recently achieved in high-quality samples. Since its first observation [3], the trion has been intensively studied, both experimentally [4] and theoretically [5]. One of the aspects that has not been considered yet is the influence of the excess of electrons in the trion properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the striking differences of optical experiments, compared to transport, is the presence of photoexcited holes in the system, which can significantly influence its properties. In samples with very low carrier concentration, the Coulomb interaction between electrons and holes leads to the formation of negatively charged excitons, which have been a subject of intense research during the past decade (see, e.g., [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]). For samples with relatively strong disorder, the commonly accepted picture is that at low density the two-dimensional electron system (2DES) breaks up into areas with finite density (electron puddles) and completely depleted regions, where neutral excitons (X 0 ) can form.…”
Section: Introductionmentioning
confidence: 99%